2021
DOI: 10.1186/s13019-021-01624-6
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nuss operation using introducer-bar complex for pectus excavatum in adults: a retrospective study

Abstract: Background Shortcoming of traditional Nuss operation on adults is gradually found in the clinical practice. A new kind of introducer-bar complex was introduced. However, there is limited evidence regarding its safety and efficacy. Therefore, a single center, retrospective study was conducted to address this issue. Methods Patients with pectus excavatum who underwent surgery between January 2015 and June 2017 were consecutively enrolled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The most common complications observed in adult patients were bar displacement, wound infection, pneumothorax, pleural effusion, reoperation, and chronic pain. Despite complications being more common with increased age, nine of 10 articles included in this review recommend the use of either a traditional or modified Nuss procedure to correct PE deformities in adult patients [ 8 - 11 , 13 - 17 ]. Kim et al reported significantly high rates of dissatisfaction in adult patients, mainly due to a higher incidence of preoperative asymmetrical deformity, which increased the risk of complications.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common complications observed in adult patients were bar displacement, wound infection, pneumothorax, pleural effusion, reoperation, and chronic pain. Despite complications being more common with increased age, nine of 10 articles included in this review recommend the use of either a traditional or modified Nuss procedure to correct PE deformities in adult patients [ 8 - 11 , 13 - 17 ]. Kim et al reported significantly high rates of dissatisfaction in adult patients, mainly due to a higher incidence of preoperative asymmetrical deformity, which increased the risk of complications.…”
Section: Reviewmentioning
confidence: 99%
“…The exclusion criteria were the following: articles in a different language, case reports, articles detailing surgical techniques, review articles, articles in which patients underwent prior surgical intervention for PE, patient population less than 18 years old, patient population with less than or equal to 10 patients, articles with incomplete data, and non-human studies. We included articles in which the Nuss procedure was performed in adult patients over the age of 18 years and in which the outcomes and complications were discussed [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Tai Chi is a traditional Chinese boxing. According to TCM, kidney deficiency is the fundamental pathogenesis of ovulation disorder infertility [135]. Tai Chi focuses on the function of "activating the waist," "waist is the house of the kidney," and the exercise of the waist helps the accumulation of the essence of the kidney [136].…”
Section: Exercisementioning
confidence: 99%